MRSA in Pigs and the Environment as a Risk for Employees in Pig-Dense Areas of Sri Lanka - Kalupahana, Ruwani S.; Duim, Birgitta; Verstappen, Koen M.; Gamage, Chandika D.; Dissanayake, Nilanthi; Ranatunga, Lakmali; Graveland, Haitske; Wagenaar, Jaap A. (Frontiers in Sustainable Food Systems, 2019)
Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) is widely spread in intensive farming systems and considered an occupational risk for humans. MRSA is a common nosocomial pathogen in Sri Lanka, but information about prevalence of MRSA in pig farming in Sri Lanka is scarce. Farming is largely a small-scale confined system, and antimicrobial use in these systems is poorly regulated with no veterinary oversight for use. This study identified on 100 pig farms a MRSA prevalence of 10%, with MRSA-positive samples in pigs, farm workers, and dust of 1.2% (6/493), 2.2% (5/228), and 0.8% (1/119), respectively. The genotypes of these strains were compared with 22 human MRSA strains from a hospital; identified in pig farms were CC1/ST1/t127, CC5/ST5/t002, CC6/ST6/t304 or t4403, singleton ST3841/t10744, of which CC1/ST1/t127 and CC/ST5/t002 were present both in isolates from pigs and humans, suggesting a human origin. LA-MRSA types associated with intensive farming (ST398, ST9) were not detected. The low MRSA prevalence at farm level (10% versus up to 70% in intensive farming systems) might be due to the management of these farms – open air and low dust. We conclude that in Sri Lanka the occupational risk for MRSA acquisition of people working with pigs is negligible.